Understanding journalism - Burns, Lynette Sheridan (SAGE, 2013)
This fully revised Second Edition of the hugely popular Understanding Journalism skilfully guides students through the various elements of journalistic practice. It takes into account recent changes in the field, most notably the roles of social media and media ethics.